The Cambridge encyclopedia of child development - Hopkins, Brian (Cambridge University Press, 2013)
The Cambridge Encyclopedia of Child Development is a definitive, accessible and up-to-date account of all aspects of child development. Written by an international team of leading experts, it adopts an interdisciplinary approach covering topics that range from neonatal development to education, encompassing pediatrics, neuroscience, theories and research methods, physical development, social development, cognitive development, psychopathology and parenting. The contributors also look at cultural issues, sex differences and the history of child development. Brian Hopkins is co-author of Crying as a Sign, a Symptom, and a Signal